2002
DOI: 10.1016/s0896-6273(02)00644-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Dynamics of Odor Representations in the Mammalian Olfactory Bulb

Abstract: We explored the spatio-temporal dynamics of odor-evoked activity in the rat and mouse main olfactory bulb (MOB) using voltage-sensitive dye imaging (VSDI) with a new probe. The high temporal resolution of VSDI revealed odor-specific sequences of glomerular activation. Increasing odor concentrations reduced response latencies, increased response amplitudes, and recruited new glomerular units. However, the sequence of glomerular activation was maintained. Furthermore, we found distributed MOB activity locked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
254
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(282 citation statements)
references
References 78 publications
23
254
2
3
Order By: Relevance
“…2C), and this for most region of the image. This time-course was consistent with previous observation of olfactory bulb intrinsic signal (Meister and Bonhoeffer, 2001;Spors and Grinvald, 2002;Wachowiak and Cohen, 2003), although in some studies clear exponential behaviour was seen only after high-pass spatial filtering. In our case and for stable recordings, no filtering was required to observe consistently this time-course.…”
Section: Intrinsic Signalsupporting
confidence: 92%
See 1 more Smart Citation
“…2C), and this for most region of the image. This time-course was consistent with previous observation of olfactory bulb intrinsic signal (Meister and Bonhoeffer, 2001;Spors and Grinvald, 2002;Wachowiak and Cohen, 2003), although in some studies clear exponential behaviour was seen only after high-pass spatial filtering. In our case and for stable recordings, no filtering was required to observe consistently this time-course.…”
Section: Intrinsic Signalsupporting
confidence: 92%
“…For fast imaging, such as voltage or calcium sensitive dyes imaging, the signal follows the rapid fluctuations of the neuronal activity, which can yield strong time-course heterogeneities among the pixels of a single recording or from experiment to experiment. For example, both voltage and calcium dye imaging in the olfactory bulb have revealed some temporal jitter between activations of different glomeruli (Spors and Grinvald, 2002;Spors et al, 2006). Unpredictable fluctuations or systematic timecourse variations are a problem for the LM fitting, but can be dealt with up to a certain extent.…”
Section: Lm-based Signal Extraction: Restrictions and Applicability Tmentioning
confidence: 99%
“…Imaging of glomeruli shows adaptation (Fig. 5) (15). One simple hypothesis would be that adaptation of ORNs would delay firing downstream.…”
Section: Discussionmentioning
confidence: 99%
“…Direct recordings of ORNs in rats show that ORNs are excited by odors and that activity can last for seconds after odor cessation (14). Others have measured the output of ORNs, by imaging glomeruli, and found that the response is gated by each breath and that the amplitude decreases with time (13,15). The importance of breath segmentation for M/T cells has recently been shown in awake subjects, where neurons respond with precise, phasic firing patterns (16)(17)(18).…”
mentioning
confidence: 99%
“…We found that dyes RH-1691, RH-1692, and RH-1838 were the best for the present application. For their chemical structure see Spors and Grinvald (2002).…”
Section: Methodsmentioning
confidence: 99%